Atopic myelitis in a European woman residing in Japan. Issue 9 (14th August 2010) - Isaacs, Jeremy D; Bodini, Benedetta; Ciccarelli, Olga; Scadding, Glenis K; Thompson, Alan J
Abstract : Nearly 100 cases of atopic myelitis have been reported in Japan. However, it has only been described in two non-Japanese patients, both from Western Europe. We report a European individual who developed cervical myelitis while resident in Japan. This showed a partial response to corticosteroids. There was no clinical or radiological dissemination for over 5 years, at which time she had a brainstem relapse caused by a new lesion in the medulla oblongata. The patient had high serum total IgE with evidence of allergy to several antigens, including house dust mite and soya. It is possible that the incidence of atopic myelitis may be underestimated where it is not standard practice to measure serum IgE levels in patients with myelopathy. Such cases will instead be subsumed into the diagnostic category of clinically isolated syndrome. However, it remains uncertain whether atopic myelitis is a distinct disease or falls within the spectrum of demyelinating diseases. Further studies are required to fully elucidate the relationship between atopy and the incidence and severity of CNS inflammatory disorders.